2020
DOI: 10.7554/elife.58567
|View full text |Cite
|
Sign up to set email alerts
|

Investigating pleiotropic effects of statins on ischemic heart disease in the UK Biobank using Mendelian randomisation

Abstract: We examined whether specifically statins, of the major lipid modifiers (statins, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors and ezetimibe) have pleiotropic effects on ischemic heart disease (IHD) via testosterone in men or women. As a validation, we similarly assessed whether a drug that unexpectedly likely increases IHD also operates via testosterone. Using previously published genetic instruments we conducted a sex-specific univariable and multivariable Mendelian randomization study in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 92 publications
(139 reference statements)
1
32
0
Order By: Relevance
“…It's result was consistent with our results. In addition, Schooling et al [46] investigated the pleiotropic effect of statins on CHD and found that the effect of statins on CHD was mediated by BT, and they found that BT was positively correlated with CHD, which was consistent with our point estimate of BT.…”
Section: Discussionsupporting
confidence: 87%
“…It's result was consistent with our results. In addition, Schooling et al [46] investigated the pleiotropic effect of statins on CHD and found that the effect of statins on CHD was mediated by BT, and they found that BT was positively correlated with CHD, which was consistent with our point estimate of BT.…”
Section: Discussionsupporting
confidence: 87%
“…Previous MR studies have suggested that calcium increases the risk of ischemic heart disease (IHD) [ 38 40 ] and SHBG reduces it [ 40 ], so these mechanisms together might have a relatively neutral effect on IHD in women. Sex-specific effects of calcium and SHBG on IHD have not been fully assessed, so how these effects would affect specifically women is unknown, although broadly statins appear to have the same effects on IHD in men and women after accounting for testosterone [ 8 ]. SHBG inactivates sex hormones, so lowering SHBG might increase the availability of sex hormones and increase the risk of any related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that some novel effects of statins have been missed, which could be addressed by repeating this study when larger sex-specific genetic studies are available. Third, we used rs12916 and associated genetic variants as a surrogate for the pharmacological effects of statins [ 12 ], which mimics a life-long small dose of endogenous statins [ 8 , 10 , 13 ], so the MR estimates represent life-long inhibition of HMGCR [ 8 , 10 ] and do not necessarily reflect the effects of statin treatment which generally starts in middle age [ 10 , 61 ]. These estimates are usually different in magnitude from the short-term effects of pharmacologic interventions in an RCT [ 62 ] although similar effect sizes have been seen for genetically mimicked statins and use of statins [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations